Return‐to‐work self‐efficacy questionnaire: Cross‐cultural adaptation and validation in China - Ting Wang; Mu Jin; Ruiqi Zhu; Li Zheng; Danni Wang; Xin Zhao; Xueping Zhao (Wiley, 2023)
Abstract Aim To develop a Chinese version of the return‐to‐work self‐efficacy (RTW‐SE‐11) and verify its reliability and validity. Design A validation study. Methods The RTW‐SE‐11 was translated into Chinese according to the Brislin's model, and then the semantic adjustment of questionnaire was carried out through multi‐field expert evaluation and preliminary investigation. Results All 11 items of the original questionnaire were retained. Content validity index (CVI) of the Chinese version of RTW‐SE‐11 indicated good validity, with Inter‐rater Agreement (IR) of 0.97, item CVI of 0.90-1.00 and questionnaire CVI of 0.91. Cronbach's α coefficient of RTW‐SE‐11 (Chinese version) was 0.923, suggesting high internal consistency, with test-retest reliability of 0.799 and half‐fold reliability of 0.926. Patient or public contribution: The Chinese version of the RTW‐SE‐11 questionnaire confirmed good reliability and validity for the assessment of return to work self‐efficacy in Chinese breast cancer patients.